A GP-AHP approach to Design Responsive Supply Chains for Pareto Customers. (2021) - Khorramshahgol, Reza; Al-Husain, Raed
Highlights: Measure the implied uncertainty of demand Prioritizes the customers based on Pareto 20-80 rule for demand fulfillment Customer Priority index matrix helps allocation of funds ABSTRACT: This research mainly aims to provide a practical method to (1) rank a firm's customers, (2) determine the implied uncertainty for customers' demand, and (3) allocate supply chain (SC) resources for meeting customer demands in an equitable manner in order to provide them with an appropriate/desired level of responsiveness. The suggested methodology utilizes the analytic hierarchy process (AHP) and the Delphi method to (1) assess customers based on their relative importance and (2) determine the implied demand uncertainty for the product(s) they purchase from the firm. The information obtained from AHP and Delphi is used to construct a goal programming (GP) model to allocate organizational resources among the customers to meet their demands.